Criação do conhecimento e inovação como variáveis mediadoras da relação entre as condições capacitadoras e o desempenho organizacional - Craco, Tânia (My University, 2017)
In this doctoral thesis we sought to identify, from a theoretical and empirical perspective, in the APLMMeA, the relations between the enabling conditions, knowledge creation, innovation and organizational performance, as well as to construct and validate a model that demonstrates the relation between these Variables. The research can be classified as quantitative, having a cross-cut, being made possible by means of a survey. The data collection was carried out by means of a questionnaire applied personally to the managers of medium and large companies belonging to APLMMeA, which is relevant Industrial pole of the region. For the purpose of this thesis the research questionnaire was elaborated based on scales already validated in previous researches. The statistical methods used were: factorial analysis, multiple correlation, regression analysis and modeling of structural equations. It was found that the enabling conditions have significant indirect effects on organizational performance through the creation of knowledge and innovation, and that knowledge creation has a significant indirect effect on organizational performance through innovation in the tested model. The theoretical contributions were: the constructed and tested model that shows the relationships between the enabling conditions, knowledge creation, innovation and organizational performance; the significant relationships of the variables that make up the enabling conditions; and the effect of multiple mediation. For the managerial area, this model contributed to a better understanding of the different variables and their respective cause and effect relationships. Therefore, the enabling conditions: autonomy, intention, redundancy, requisite variety, fluctuation and creative chaos presented a relationship between that reflected positively in the creation knowledge and innovation, so these conditions must be stimulated in the strategic formulation by the management. For future studies it is suggested to carry out longitudinal studies, to include moderating variables in the proposed model, to create scales and to apply qualitative research as a way to deepen the data obtained (sic).
Nesta tese procurou-se identificar, sob uma perspectiva teórica e empírica, no APLMMeA, as relações entre as condições capacitadoras, a criação do conhecimento, a inovação e o desempenho organizacional, bem como construir e validar um modelo que demonstrasse a relação entre estas variáveis. A pesquisa pode ser classificada como quantitativa, tendo um recorte transversal, sendo viabilizado por meio de uma survey; a coleta de dados foi realizada por meio de um questionário aplicado pessoalmente aos gestores das empresas de médio e grande porte pertencentes ao APLMMeA, que é um relevante polo industrial da região. Para fins desta tese, o questionário de pesquisa foi elaborado com base em escalas já validadas em pesquisas anteriores. Os métodos estatísticos empregados foram: análise fatorial, correlação múltipla, análise de regressão e modelagem de equações estruturais. Verificou-se que as condições capacitadoras possuem efeitos indiretos significativos sobre o desempenho organizacional por meio da criação do conhecimento e da inovação e que a criação do conhecimento possui efeito indireto significativo sobre o desempenho organizacional, por meio da inovação no modelo testado. As contribuições teóricas encontradas foram: o modelo construído e testado que mostra as relações entre as condições capacitadoras, criação do conhecimento, inovação e desempenho organizacional, as relações significativas das variáveis que compõem as condições capacitadoras e o efeito da mediação múltipla. Para a área gerencial, o referido modelo contribuiu para uma melhor compreensão das diferentes variáveis e suas respectivas relações de causa e efeito. Por conseguinte, as condições capacitadoras: : autonomia, intenção, redundância, variedade de requisitos e flutuação e caos criativo apresentaram relação entre si, o que refletiu positivamente na criação do conhecimento e na inovação, logo, essas condições devem ser estimuladas na formulação estratégica pela gestão. Para estudos futuros sugere-se realizar estudos longitudinais, incluir variáveis moderadoras no modelo proposto, criar escalas e aplicar pesquisa qualitativa como forma de aprofundamento dos dados obtido (sic).
Keywords: Gestão do conhecimento; Desenvolvimento organizacional; Capital intelectual; Knowledge management; Organizational change; Intellectual capital